The right microbe-associated molecular patterns for effective recognition by plants - Lü, Pengpeng; Liu, Yi; Yu, Xixi; Shi, Chun-Lin; Liu, Xiaokun (Frontiers in Microbiology, 2022)
Plants are constantly exposed to diverse microbes and thus develop a sophisticated perceive system to distinguish non-self from self and identify non-self as friends or foes. Plants can detect microbes in apoplast via recognition of microbe-associated molecular patterns (MAMPs) by pattern recognition receptors (PRRs) on the cell surface to activate appropriate signalling in response to microbes. MAMPs are highly conserved but essential molecules of microbes and often buried in microbes’ complex structure. Mature MAMPs are released from microbes by invasion-induced hydrolytic enzymes in apoplast and accumulate in proximity of plasma membrane-localized PRRs to be perceived as ligands to activate downstream signalling. In response, microbes developed strategies to counteract these processing. Here, we review how the formation, the concentration, and the size of mature MAMPs affect the PRR-mediated immune signalling. In particular, we describe some potential applications and explore potential open questions in the fields.